Effect of porosity on the Seebeck coefficient of mesoporous TiO2 thin films - Ha, Tae-Jung; Park, Hyung-Ho; Jung, Sin-Young; Yoon, Seok-Jin; Kim, Jin-Sang; Jang, Ho Won (ELSEVIER SCIENCE SA, 2010)
Mesoporous TiO2 films were prepared by using titanium tetraisopropoxide as the titania precursor and triblock copolymer as the structure directing agent. The synthesized mesoporous TiO2 film was confirmed to have the ordered pore structure with rutile phase by small angle and wide angle X-ray diffraction analyses. The mesoporous TiO2 film has the porosity range from 21.6 to 35.6%, and its Seebeck coefficient was changed according to its porosity, up to -88.6 mu V/K. From the obtained Seebeck coefficient, the ordered mesoporous TiO2 film was found to be a good candidate of thermal sensing layer of thin film thermal sensor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: MOLECULAR-SIEVES; TITANIA